Oral health in Brazil: the challenges for dental health care models - Sônia Cristina Lima Chaves (Sociedade Brasileira de Pesquisa Odontológica, 2012)
This paper discusses adult oral health in Brazil according to three perspectives: 1) the available epidemiological evidence about the population's oral-health-related epidemiological situation, especially adults and the elderly population, in relation to two high prevalence oral injuries (dental caries and tooth loss), 2) the main health care models for dealing with this situation, by analyzing the related historical processes in order to reveal the likely social, political and epidemiological implications of the different models, and 3) lastly, the possible challenges to Brazilian dentistry or collective oral health in overcoming these obstacles. The main results of the study indicate that, from an epidemiological point of view, Brazil is undergoing a transition in dental caries and tooth loss, which is not yet reflected in the profile of the elderly, but which is tentatively evidenced in young adults. Tooth loss remains high. Certain aspects of society's economic and political superstructure have an important impact on oral health indicators and existing inequalities. Oral health care models have a relative importance and must not be neglected. Vestiges of ideological movements, like preventive medicine, may explain the current impasse in collective oral health practices, such as the preeminence of Finalized Treatment (FT) in clinics and of preventive care in schools fostered by community-based programs. It is therefore important to develop conceptual, theoretical reflections and to increase the objects of intervention, their purposes and their modus operandi. The practice of dentistry according to these alternative models is still being constructed. New studies related to the different formats of these new practices are recommended.